1992
DOI: 10.1021/j100187a043
|View full text |Cite
|
Sign up to set email alerts
|

Formation of nanoparticulate iron(III) oxide-stearate multilayer through Langmuir-Blodgett method

Abstract: tional energy at the T site is 145 meV in the present calculation and 152 meV in the zeroth-order approximation. The energy at the 0 site is 43 meV in the present calculation and 86 meV in the zeroth-order approximation. By the inelastic neutron scattering measurements the vibrational energy of hydrogen in the bulk a-zirconium at 873 K was obtained to be 144 meV, and the energy spread (fwhm of the peak) is 47 meVn2' It has been found that the calculated vibrational energy at the T site is in good agreement wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(51 citation statements)
references
References 4 publications
2
49
0
Order By: Relevance
“…For example, the C --C stretching deformation of the quinoid (1 562 cm À1 ) and benzenoid rings (1 479 cm À1 ), the C-N stretching of the secondary aromatic amine (1 293 cm À1 ), the aromatic C-H in-plane bending (1 116 cm À1 ), and the out-of-plane deformation of C-H in the 1,4-disubstituted benzene ring (802 and 508 cm À1 ) are observed. [14] The UV-vis absorption spectra of the composite nanofibers dissolved in de-ionized water further proved this result ( Figure 2 [3] ). For example, two peaks at 440 and 900 nm with a long tail, which are assigned to polaron bands, are observed, [15] indicating that the composite nanofibers are identical to the emeraldine salt form of PANI.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…For example, the C --C stretching deformation of the quinoid (1 562 cm À1 ) and benzenoid rings (1 479 cm À1 ), the C-N stretching of the secondary aromatic amine (1 293 cm À1 ), the aromatic C-H in-plane bending (1 116 cm À1 ), and the out-of-plane deformation of C-H in the 1,4-disubstituted benzene ring (802 and 508 cm À1 ) are observed. [14] The UV-vis absorption spectra of the composite nanofibers dissolved in de-ionized water further proved this result ( Figure 2 [3] ). For example, two peaks at 440 and 900 nm with a long tail, which are assigned to polaron bands, are observed, [15] indicating that the composite nanofibers are identical to the emeraldine salt form of PANI.…”
Section: Resultsmentioning
confidence: 55%
“…[3] Up to date, polyaniline (PANI) nanotubes containing Fe 3 O 4 nanoparticles (%10 nm in diameter) has been firstly prepared by a template-free method in the presence of Fe 3 O 4 nanoparticles. [4] The magnetic nanoparticles in that method are co-structured with oxidation polymerization of aniline to form the PANI/Fe 3 O 4 nanotubes via a self-assembly process.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] In fact, composites of conducting polymers containing magnetic particles have many potential applications in electromagnetic interference shielding, 10 electrochromic devices, 11 and nonlinear optical systems. 12 Until now, many studies on composites with electromagnetic properties have been reported. Yoneyama et al 13 and Partch et al, 14 for example, reported the incorporation of metal oxide particles into polypyrrole during electropolymerization.…”
Section: Introductionmentioning
confidence: 99%
“…LB technique has proved to be an efficient tool for fabrication of organized interfacial two-dimensional arrays of proteins [156,157], ligand-stabilized inorganic nanoclusters [158][159][160], nanoparticles [161][162][163][164][165][166][167][168][169][170][171][172][173][174][175], BaCrO 4 nanorods [85], metal and semiconductor nanowires [83,84] and carbon nanotubes [176] as well as corresponding multilayer structures. Nanoparticulate LB films were used to form patterned structures on surfaces [177] via bsoft lithographyQ approach introduced by Zhao et al [178] at Harvard.…”
Section: Organized Planar Inorganic and Hybrid Organic-inorganic Nanomentioning
confidence: 99%